ANALISIS PERHITUNGAN HARGA POKOK PRODUKSI MENGGUNAKAN METODE PROSESS COSTING UNTUK MENENTUKAN HARGA JUAL PADA UMKM MOCHI MADIUN - Liana Rahmawati; Nadila Eka Prahastiwi; Albryan Wahyu Andita; Halleina Rejeki Putri Hartono (Musytari : Jurnal Manajemen, Akuntansi, dan Ekonomi, 2024)
This study focuses on the calculation of production costs using the process costing method to determine the selling price of products at UMKM Mochi Madiun, a micro-enterprise producing mochi based in Madiun, Indonesia. Accurate calculation of production costs, including raw materials, labor, and factory overhead, is crucial for pricing and profitability. The study reveals inefficiencies in the traditional costing methods employed by the business, which overlooked certain overhead costs, leading to imprecise pricing decisions. By applying the process costing method, the research recalculated production costs, finding a total production cost of IDR 15,071,998 for 3,000 units, resulting in an average cost of IDR 5,024 per unit. This method provided a more detailed and accurate breakdown of costs, highlighting its potential to enhance financial management and decision-making for similar enterprises.